THE EU EASTERN PARTNERSHIP INITIATIVE AS A TOOL FOR SUPPORTING LOCAL GOVERNMENT REFORM IN THE COUNTRIES OF THE “ASSOCIATED TRIO” - Tsebenko, Oleh; Fedirko, Bohdan (Public Management and Policy, 2026)
The article analyzes the role of the EU Eastern Partnership Initiative in supporting local self-government and decentralization reforms in Ukraine, Moldova, and Georgia. It examines the peculiarities of implementing local government reforms in the “Associated Trio” countries. The Eastern Partnership Index is used to examine the dynamics of the country’s convergence with EU standards in the field of local self-government. It has been found that Ukraine and Moldova are showing positive dynamics in the implementation of EU standards and norms in this area in 2021–2025, while Georgia is seeing a slowdown in reforms. The features of the EU’s Eastern Partnership Initiative were analyzed, and it was noted that this Eastern policy is aimed at bringing the countries of the region closer to the EU, their democratization, economic development, implementation of reforms, strengthening economic stability, good governance, and strengthening people-to-people contacts. The internal and external challenges that hinder EU support for decentralization reforms in the “Associated Trio” countries are identified. In particular, the biggest challenges include the lack of a unified EU position on the countries of the region, the slowdown of local self-government reforms by the countries themselves, corruption, geopolitical challenges in the region, the factor of the Russian Federation, and the decline in the level of democracy. The level of local self-government reforms implementation in the countries of the “Associated Trio” was studied, and it was found that Ukraine is the most reformed in this area, while Georgia has the lowest level of implementation. Recommendations are made on strengthening the role of the EU and its Eastern Partnership instrument in the implementation of local self-government reforms in Ukraine, Georgia, and Moldova. The prospects for the integration of the “Associated Trio” countries into EU standards in the field of local self-government are highlighted and three scenarios are identified.